1991
DOI: 10.1103/physrevlett.67.2167
|View full text |Cite
|
Sign up to set email alerts
|

Diffuse x-ray scattering study of an oxygen-disordered tetragonal YBa_{2}(Cu_{0.955}Al_{0.045})_{3}O_{7} crystal

Abstract: X-ray scattering from a tetragonal single crystal of YBa2(Cuo.955Alo.o45)3C>7 shows diffuse streaking in [110] directions about the Bragg peaks. Through a quantitative calculation using a coupled concentration wave, static displacement wave approach, we show that this is essentially attributable to the shear displacement field produced by a disordered oxygen array on the Cu(0-O "chain" plane. We also observe pronounced short-range chain order (local orthorhombic fluctuations) whose correlation range is consid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

1992
1992
1994
1994

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(15 citation statements)
references
References 28 publications
1
12
0
Order By: Relevance
“…Skjerpe et al 1992) showed, by kinematical calculations of the diffraction intensities, that YBa,Cu,O, with an average domain size below about 20 nm will appear tetragonal when only the fundamental reflections are considered. On the other hand, through calculations using a coupled concentration wave-static displacement wave approach, Jiang et al (1991) and Cai, Zhu and Welch (1992) generated excellent matches of intensity profile of the diffuse scattering in the a*-b* plane to that observed in X-ray and TEM experiments. They concluded that the shear displacement field (Huang scattering) produced by randomly distributed oxygen (Jiang et al 1991) or oxygen clustering (Cai et al 1992) on the C u ( l k 0 'chain' plane is responsible for diffuse streaking in [llO] and [TlO] directions through the Bragg peaks.…”
Section: Q 1 Introductionmentioning
confidence: 77%
See 3 more Smart Citations
“…Skjerpe et al 1992) showed, by kinematical calculations of the diffraction intensities, that YBa,Cu,O, with an average domain size below about 20 nm will appear tetragonal when only the fundamental reflections are considered. On the other hand, through calculations using a coupled concentration wave-static displacement wave approach, Jiang et al (1991) and Cai, Zhu and Welch (1992) generated excellent matches of intensity profile of the diffuse scattering in the a*-b* plane to that observed in X-ray and TEM experiments. They concluded that the shear displacement field (Huang scattering) produced by randomly distributed oxygen (Jiang et al 1991) or oxygen clustering (Cai et al 1992) on the C u ( l k 0 'chain' plane is responsible for diffuse streaking in [llO] and [TlO] directions through the Bragg peaks.…”
Section: Q 1 Introductionmentioning
confidence: 77%
“…On the other hand, through calculations using a coupled concentration wave-static displacement wave approach, Jiang et al (1991) and Cai, Zhu and Welch (1992) generated excellent matches of intensity profile of the diffuse scattering in the a*-b* plane to that observed in X-ray and TEM experiments. They concluded that the shear displacement field (Huang scattering) produced by randomly distributed oxygen (Jiang et al 1991) or oxygen clustering (Cai et al 1992) on the C u ( l k 0 'chain' plane is responsible for diffuse streaking in [llO] and [TlO] directions through the Bragg peaks. They also suggested that there were local orthorhombic fluctuations or orthorhombic domains in Fe-, Co-or Al-alloyed YBa,Cu,O, -& Twinning involves a shear displacement.…”
Section: Q 1 Introductionmentioning
confidence: 77%
See 2 more Smart Citations
“…8,4,20 This will produce a free energy difference (F − − F + )(x, y) which will depend on gradients of η. 2 The local elastic free energy can in general have three minima: two at ±φ 0 for the two martensitic variants, and one at φ = 0 for the austenite.…”
mentioning
confidence: 99%